2021
DOI: 10.26603/001c.18803
|View full text |Cite
|
Sign up to set email alerts
|

Normative Parameters of Gastrocnemius Muscle Stiffness and Associations with Patient Characteristics and Function

Abstract: Background BackgroundQuantifying muscle stiffness may aid in the diagnosis and management of individuals with muscle pathology. Therefore, the primary purpose of this study was to establish normative parameters and variance estimates of muscle stiffness in the gastrocnemius muscle in a resting and contracted state. A secondary aim was to identify demographic, anthropometric, medical history factors, and biomechanical factors related to muscle stiffness. Methods MethodsStiffness of the gastrocnemius muscle was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
3
1
Order By: Relevance
“…A second key observation of our study was that no association (only exception: M2 at 10 mm: weight) was found between tissue stiffness and person characteristics. This is in contrast to earlier studies reporting significant correlations between soft tissue stiffness and sex [ 18 , 65 , 66 ], age [ 17 , 65 , 66 ] or BMI [ 9 ]. Interestingly, the study by Wilke et al [ 5 ] also failed to identify a relationship of stiffness and BMI or sex.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…A second key observation of our study was that no association (only exception: M2 at 10 mm: weight) was found between tissue stiffness and person characteristics. This is in contrast to earlier studies reporting significant correlations between soft tissue stiffness and sex [ 18 , 65 , 66 ], age [ 17 , 65 , 66 ] or BMI [ 9 ]. Interestingly, the study by Wilke et al [ 5 ] also failed to identify a relationship of stiffness and BMI or sex.…”
Section: Discussioncontrasting
confidence: 99%
“…In recent years, soft tissue stiffness, the resistance of biological structures to an external deforming force [ 1 , 2 , 3 , 4 , 5 ], has attracted increasing interest among researchers and clinicians working with patients and athletes. This is mainly due to early evidence suggesting that the stiffness of the muscular and connective tissue may help identify pathological tissue states [ 1 , 2 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ], monitor therapy or training effects [ 13 , 14 , 15 , 16 , 17 , 18 ] or prevent sports injury [ 19 , 20 , 21 ]. However, in the daily routine, most physiotherapists or trainers do not have access to sophisticated and complex measurement technologies (e.g., elastography) and thus, there is a need for straightforward and easy-to-handle devices capturing biomechanical soft tissue properties.…”
Section: Introductionmentioning
confidence: 99%
“…In another recent study, the relationships between gastrocnemius muscle stiffness, BMI, and other factors (e.g., age, race, anxiety) were investigated in healthy individuals 18-50 years of age. No association was found between BMI and gastrocnemius muscle stiffness at rest or during contraction [33]. In a study comparing the viscoelastic properties of erector spinae muscle in patients with ankylosing spondylitis versus healthy controls, a weak correlation was found between BMI and viscoelastic properties in patients with ankylosing spondylitis.…”
Section: Discussionmentioning
confidence: 94%
“…36 The BAI has demonstrated adequate reliability and validity when compared to other anxiety questionnaires and anxiety assessed with this measure has been shown to demonstrate a negative relationship with muscle stiffness. 36,37 Upon completion of questionnaires, participants with LBP received a subjective and neuromusculoskeletal exam to determine their appropriateness for the study.…”
Section: Methodsmentioning
confidence: 99%